Determinação do perfil metabolômico de pacientes infectados pelo HIV e sua relação com história natural da doença e resposta imunológica ao tratamento - Scarpellini, Bruno Correia [UNIFESP] (2018)
Introduction: HIV1 infection results in a longlasting activation of the immune system and inflammation leading to a profound imbalance in the functions related to cellular metabolism in infected patients despite the use of antiretrovirals (ART). Objective: To determine a possible plasma biosignature that could be related to HIV infection; the rate of progression of HIV disease; the immune response to treatment; inflammation; the metabolic repercussion of natural control and ART with viremia; the cumulative damage of HIV in the human organism according to distinct patterns of disease progression and to assess whether artificial suppression of viremia (ART) promotes metabolomic patterns distinct from the natural suppression of infection. Methods: A quantitative quantitative tandem mass spectrometry metabolomic approach was used in 20 HIVinfected and 17 nonHIVinfected controls. Results: Twentyfive unique metabolites were identified and distinguished those infected by HIV from the negative controls. Changes in the metabolism of hydroxylation and carboxylation were observed; branched chain amino acid catabolism, lysine, organic acids, tryptophan and glutamine. Five metabolites were able to predict disease progression. The results point to a possible inborn error of metabolism (MADD) and a correlation with the control of HIV replication and a functional cure of HIV (elite controllers or CEs). Pretreatment levels of phosphatidylcholines were able to predict the immune response to ART. Despite the natural control of viremia, CEs presented cumulative damage to the body, with increased acylcarnitine concentrations corroborating HIVinduced mitochondrial dysregulation. In patients who control viremia with ART, it was observed a decrease in βoxidation, decreased levels of phospholipases A2 (reduction of inflammation), and recovery of FADS1 levels. Conclusions: The results show that, in addition to their usefulness as reliable biomarkers of HIV infection, the metabolic profiles of HIVinfected individuals can provide clues about the mechanism of inflammation, permanent tissue damage, and damage to HIV related organs. Moreover, they can very accurately and early predict who will progress or not to disease or who may progress to a state of nonimmune response to ART and that the artificial suppression of viremia with ART is more beneficial than the natural suppression of proportionate viremia by the "functional cure" that occurs in the EC.